SOLO TECHNO PARK SEBAGAI UPAYA PENGEMBANGAN SDM DAERAH - N. J, AN NISA PUTRI; Harsasto, Priyatno; Adnan, Muhammad (Journal of Politic and Government Studies, 2018)
Indonesia lagging behind in the global competition compared with other countries. The lag is due to the lack of quality of human resource development (HRD). The local government to build a region-based technology to overcome the backwardness through training and business incubation program. The purpose of this study was describe and explain the development of training and business incubation in human resource development (HRD) and the mechanism of human resource development (HRD) through local governments.The method used is a qualitative approach to data collection techniques are observation, interview and documentation. Informants in this study is the Head of Research and Development Bappeda Kota Surakarta, Division of Public Administration and Personnel STP, Division of Training and Teaching Factory STP, and Staff ATMI.The results showed that (1) Development of training and business incubation is very effective to improve the quality and quantity of human resources development. (2) The program Solo Techno Park were able to develop a number of new entrepreneurs in technology. (3) Development of human resources through the local government carried out by way of promotion and training.Â Keywords: human resource development, training and business incubation program